Optimization of the Electricity Economics System (EES) in Supporting National Energy Policy Using a Tri-Level Programming Approach - Anita Talia; Lasker Pangarapan Sinaga (Program Studi Matematika, Universitas Tadulako, 2026)
High electricity subsidies in the national budget (APBN) pose a challenge to national fiscal sustainability. This research aims to formulate an optimization model for the Electricity Economics System (EES) that hierarchically balances the interests of the government, consumers, and producers. The methodology employs a Tri-Level Programming approach with a nested optimization strategy. Simulation results demonstrate that the model reached a stable convergence point at the 41st iteration with a zero relative change value. The national subsidy allocation was significantly reduced from IDR 68.64 trillion to IDR 24.03 trillion. Thus, this model serves as a strategic decision-making instrument that effectively represents hierarchical interactions between energy actors to produce more efficient fiscal policy solutions and support the sustainability of the national power system.